2015
DOI: 10.1074/jbc.m115.651810
|View full text |Cite
|
Sign up to set email alerts
|

The Homeodomain Transcription Factors Antennapedia and POU-M2 Regulate the Transcription of the Steroidogenic Enzyme Gene Phantom in the Silkworm

Abstract: Background:The transcriptional regulation of steroidogenic enzymes in the silkworm remains poorly understood. Results: Antp and POU-M2 are expressed in the PG and regulate the transcription of Phantom. Conclusion: Antp and POU-M2 coordinate the transcription of Phantom via a protein interaction. Significance: Our study indicates new roles for homeodomain proteins in regulating insect ecdysteroidogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 72 publications
2
29
0
Order By: Relevance
“…Such gene expressions are induced and/or maintained by a number of TFs, hereinafter referred to as "ecdysteroidogenic TFs". Some but not all ecdysteroidogenic TFs directly bind to the promoters of ecdysteroidogenic genes, confirmed by an electrophoresis mobility shift assay or chromatin immunoprecipitation assay (Xiang et al 2010;Deng & Kerppola 2013;Danielsen et al 2014;Meng et al 2015). The known validated and putative ecdysteroidogenic TFs required in the PG are listed in Table 1.…”
Section: Transcription Factors Are Required For Expression Of Ecdystementioning
confidence: 85%
See 2 more Smart Citations
“…Such gene expressions are induced and/or maintained by a number of TFs, hereinafter referred to as "ecdysteroidogenic TFs". Some but not all ecdysteroidogenic TFs directly bind to the promoters of ecdysteroidogenic genes, confirmed by an electrophoresis mobility shift assay or chromatin immunoprecipitation assay (Xiang et al 2010;Deng & Kerppola 2013;Danielsen et al 2014;Meng et al 2015). The known validated and putative ecdysteroidogenic TFs required in the PG are listed in Table 1.…”
Section: Transcription Factors Are Required For Expression Of Ecdystementioning
confidence: 85%
“…; Meng et al . ). The known validated and putative ecdysteroidogenic TFs required in the PG are listed in Table .…”
Section: Transcription Factors Are Required For Expression Of Ecdystementioning
confidence: 97%
See 1 more Smart Citation
“…Deng and colleagues reported that BmBrC‐Z4 is an up‐stream regulator of BmPOUM2 but that the two do not directly interact (Deng et al ., ), and that BmPOUM2 plays a role in regulating the wing disc culticle protein 4 (WCP4) gene expression (Deng et al ., ). BmPOUM2 participates in regulating steroidogenic enzyme genes to control ecdysteroidogenesis (Meng et al ., ). In this study, we confirmed that a key member of the Hox family of transcription factors in the silkworm, BmPOUM2, participates in the regulation of BmVg expression.…”
Section: Discussionmentioning
confidence: 97%
“…() showed that BmPOUM2 takes part in regulating the expression of the genes encoding wing disc cuticle proteins during silkworm metamorphosis. Furthermore, BmPOUM2 was found to participate in regulating steroidogenic enzyme genes to control ecdysteroidogenesis (Meng et al ., ).…”
Section: Introductionmentioning
confidence: 99%